Los espacios de representación teatral en el palacio del Buen Retiro durante el reinado de Felipe IV y el valimiento del conde-duque de Olivares - Mercedes Simal López (Mélanges de la Casa de Velázquez)
With the inauguration of the palace in December 1633, Philip IV of Spain had a new royal household where he could enjoy nature and all kinds of entertainment, without having to leave the court. Having been conceived for leisure, and therefore exempt from hosting official crown ceremonies—except for specific occasions—and lacking spaces for offices with the Councils, the interiors of the palace lent themselves to different uses and, in some cases, constituted interesting typological novelties from the architectural point of view. Throughout this article we analyse the different areas of the royal site that were used for theatrical performances during the administration of the Count-Duke of Olivares (1630-1643), including the Coliseum, a special hall designed to host permanent shows of this kind for the first time in a palace.